1995
DOI: 10.1016/0014-5793(95)00815-q
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin‐A is a zinc‐dependent DNA binding protein in macrophages

Abstract: The association of cyclosporin A (CsA) immunosuppression with inhibition of transcription factor-dependent lymphokine gene activation formed the basis of our decision to investigate nuclear-associated Cyp isoforms. Immunofluorescence microscopy of mouse macrophages cell line with a monoclonal antibody mAb7F1 raised against CypA shows a co-localisation of CypA in the nucleus and in the cytosol. Nuclear CypA binds to DNA in a zinc ion-dependent manner, in contrast to recombinant CypB. Peptidyl-prolyl cisltrans i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…There was no reaction of SLA with mAb 7F1. The mAb 7F1 is highly specific for CypA from mammalian cells and therefore a contamination with rabbit blood cells from the culture system can be excluded (Krummrei et al, 1995). In contrast, three proteins from SLA with apparent molecular masses (MM) of 19, 20 and 22 kDa cross-reacted with the polyclonal antibodies against CypB (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no reaction of SLA with mAb 7F1. The mAb 7F1 is highly specific for CypA from mammalian cells and therefore a contamination with rabbit blood cells from the culture system can be excluded (Krummrei et al, 1995). In contrast, three proteins from SLA with apparent molecular masses (MM) of 19, 20 and 22 kDa cross-reacted with the polyclonal antibodies against CypB (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon may have several explanations. First, data from ourselves and others (Bergsma et al, 1991;Krummrei et al, 1995) revealed the presence of other cyclophilin isoforms in MP, rendering it possible that additional deprivation of these cyclophilins would further enhance the antileishmanial activity. However, our attempts to reduce further the expression of other cyclophilins (CypC) proved increasingly lethal for MP (data not shown).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Samples were incubated for 5 h at room temperature with gentle rotation. Studies in our laboratory have shown that HeLa nuclei incubated under these conditions undergo very little spontaneous chromatin degradation (41).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that both Roc1 and CypA, like their mammalian homologs, are present in both the cytosol and the nucleus of Arabidopsis. CyPs also function as DNA binding proteins (50) and have been implicated in the regulation of apoptosis because of their nuclease activity, which is independent of their PPIase activity (49). Integration of the T-DNA involves illegitimate recombination in plants which usually includes small deletions of the plant DNA at target sites (51), suggesting that a nuclease function is needed for T-DNA integration into the plant genome.…”
Section: Discussionmentioning
confidence: 99%